Subretinal Implantation of Human Primary RPE Cells Cultured on Nanofibrous Membranes in Minipigs - Lytvynchuk, Lyubomyr; Ebbert, Annabelle; Studenovska, Hana; Nagymihály, Richárd; Josifovska, Natasha; Rais, David; Popelka, Štěpán; Tichotová, Lucie; Nemesh, Yaroslav; Čížková, Jana; Juhásová, Jana; Juhás, Štefan; et al. (Biomedicines, 2022)
PURPOSE: The development of primary human retinal pigmented epithelium (hRPE) for clinical transplantation purposes on biodegradable scaffolds is indispensable. We hereby report the results of the subretinal implantation of hRPE cells on nanofibrous membranes in minipigs. METHODS: The hRPEs were collected from human cadaver donor eyes and cultivated on ultrathin nanofibrous carriers prepared via the electrospinning of poly(L-lactide-co-DL-lactide) (PDLLA). "Libechov" minipigs (12-36 months old) were used in the study, supported by preoperative tacrolimus immunosuppressive therapy. The subretinal implantation of the hRPE-nanofibrous carrier was conducted using general anesthesia via a custom-made injector during standard three-port 23-gauge vitrectomy, followed by silicone oil endotamponade. The observational period lasted 1, 2, 6 and 8 weeks, and included in vivo optical coherence tomography (OCT) of the retina, as well as post mortem immunohistochemistry using the following antibodies: HNAA and STEM121 (human cell markers); Bestrophin and CRALBP (hRPE cell markers); peanut agglutining (PNA) (cone photoreceptor marker); PKCα (rod bipolar marker); Vimentin, GFAP (macroglial markers); and Iba1 (microglial marker). RESULTS: The hRPEs assumed cobblestone morphology, persistent pigmentation and measurable trans-epithelial electrical resistance on the nanofibrous PDLLA carrier. The surgical delivery of the implants in the subretinal space of the immunosuppressed minipigs was successfully achieved and monitored by fundus imaging and OCT. The implanted hRPEs were positive for HNAA and STEM121 and were located between the minipig's neuroretina and RPE layers at week 2 post-implantation, which was gradually attenuated until week 8. The neuroretina over the implants showed rosette or hypertrophic reaction at week 6. The implanted cells expressed the typical RPE marker bestrophin throughout the whole observation period, and a gradual diminishing of the CRALBP expression in the area of implantation at week 8 post-implantation was observed. The transplanted hRPEs appeared not to form a confluent layer and were less capable of keeping the inner and outer retinal segments intact. The cone photoreceptors adjacent to the implant scaffold were unchanged initially, but underwent a gradual change in structure after hRPE implantation; the retina above and below the implant appeared relatively healthy. The glial reaction of the transplanted and host retina showed Vimentin and GFAP positivity from week 1 onward. Microglial activation appeared in the retinal area of the transplant early after the surgery, which seemed to move into the transplant area over time. CONCLUSIONS: The differentiated hRPEs can serve as an alternative cell source for RPE replacement in animal studies. These cells can be cultivated on nanofibrous PDLLA and implanted subretinally into minipigs using standard 23-gauge vitrectomy and implantation injector. The hRPE-laden scaffolds demonstrated relatively good incorporation into the host retina over an eight-week observation period, with some indication of a gliotic scar formation, and a likely neuroinflammatory response in the transplanted area despite the use of immunosuppression.
Keywords: nanofibrous PDLLA membranes; minipigs; human primary RPE; subretinal implantation